Basal levels of 17-hydroxyprogesterone can distinguish children with isolated precocious pubarche. (October 2018) - Grandone, Anna; Marzuillo, Pierluigi; Luongo, Caterina; Toraldo, Roberto; Mariani, Michela; Miraglia del Giudice, Emanuele; Perrone, Laura
Abstract Background Basal levels of androgens, in particular 17-hydroxyprogesterone (17OHP), are widely debated as predictors of non-classical congenital adrenal hyperplasia (NCCAH) among patients with precocious pubarche (PP). Many authors have recommended the use of adrenocorticotropic hormone (ACTH) stimulation test in children with PP. The aim of our study was to identify clinical and biochemical predictors of NCCAH in children with PP. Methods We conducted a prospective study of 92 patients with PP undergoing an ACTH stimulation test. We tested the association of basal clinical and biochemical parameters with NCCAH diagnosis. Patients were suspected to have NCCAH if their stimulated 17OHP plasma levels were >10 ng/mL. In these patients, the diagnosis was confirmed by genetic test. Results Seven (7.6%) patients resulted having NCCAH. The best basal biochemical predictor for NCCAH was 17OHP level >2 ng/mL. In fact, a basal 17OHP level >2 ng/mL had 100% (95% confidence interval (CI), 59.04–100) sensitivity and 93% (95% CI, 85.3–97.37) specificity. The area under the receiver-operating characteristic curve for 17OHP was 0.99 (95% CI, 0.98–1.007). Conclusions Basal 17OHP cut-off of 2 ng/mL was very effective in predicting NCCAH among our patients with PP. Assay-specific cut-off would probably be the best strategy to avoid unnecessary ACTH test.